Experimental investigation on characteristics of cavitation-induced vibration on the runner of a bulb turbine. (15th April 2023) - Feng, Jianjun; Liu, Boxing; Luo, Xingqi; Zhu, Guojun; Li, Kang; Wu, Guangkuan
Abstract: Cavitation may result in reduced efficiency, increased noise and vibration and weight loss of a hydraulic turbine when local pressure is lower than the vaporization pressure. In this paper, a synchronous test system including high-speed camera and Laser Doppler Vibrometer (LDV) is established to analyze characteristics of cavitation-induced vibration on the runner of a bulb turbine under different cavitation states. The results show that the peak-to-peak and Root Mean Square (RMS) values of vibration velocities on the turbine runner both increase with the severity of cavitation, but the growth rate is remarkably different which strongly depends on the cavitation state. The runner vibration velocity holds a normal distribution for all cavitation states, and the variance of the normal distribution increases gradually with the severity of cavitation. The increase of cavitation level is accompanied by frequency band migration of vibration signals. In the state of complete cavitation, the local energy extreme of the medium-high frequency component of the runner vibration velocity signal migrates to the low frequency region, resulting in an obvious increase in the energy of the low frequency region.